IMPROVING EFFICIENCY AND EFFECTIVENESS OF CONSULTATION PROCESS BETWEEN LECTURERS AND STUDENTS THROUGH AN INFORMATION SYSTEM SOFTWARE BASED INTRANET - susana limanto; Ellysa Tjandra (Faculty of Computer Science Universitas Indonesia, 2011)
Students need to consult their problem such as final projects, academic problem, or personal problems to their lecturers. This consultation’s processes are helped by administrative staffs that make the processes relatively slow due to the high workload of the staffs. Therefore, this research tries to address this problem by creating intranet based information system to reduce the role of administrative staffs. This system provide several features such as schedule the regular consultation by lecturers, schedule the addition consultation by lecturers, cancel a scheduled consultations, change the schedule of consultations by lecturers, register for consultation by students, record the implementation consulting by lecturers, and reports. The consultation software was implemented at Informatics Engineering department, University ‘X’ for one month. After one month, a test was conducted involving five lecturers and twenty students. Testing result showed that the consultation process becomes more efficient, effective and satisfying. Mahasiswa perlu berkonsultasi mengenai masalah mereka seperti tugas akhir, masalah akademik, atau masalah pribadi kepada dosen mereka. Proses konsultasi ini dibantu oleh staf administrasi yang membuat proses relatif lambat karena beban kerja yang tinggi dari staf. Oleh karena itu, penelitian ini mencoba untuk mengatasi masalah ini dengan menciptakan sistem informasi berbasis intranet untuk mengurangi peran staf administrasi. Sistem ini menyediakan beberapa fitur seperti menjadwalkan konsultasi rutin oleh dosen, jadwal konsultasi Selain oleh dosen, membatalkan konsultasi dijadwalkan, mengubah jadwal konsultasi dengan dosen, mendaftar untuk konsultasi oleh siswa, merekam pelaksanaan konsultasi dengan dosen, dan laporan. Perangkat lunak konsultasi diterapkan di departemen Teknik Informatika, Universitas ‘X’ selama satu bulan. Setelah satu bulan, tes dilakukan melibatkan lima dosen dan dua puluh siswa. Hasil pengujian menunjukkan bahwa proses konsultasi menjadi lebih efisien, efektif dan memuaskan.